2021
DOI: 10.1002/adma.202105156
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Supramolecular Cavities Molecularly Homogenized in Polymer Membranes for Ultraefficient Precombustion CO2 Capture

Abstract: Processable molecular‐sieving membranes are important materials for realizing energy‐efficient precombustion CO2 capture during industrial‐scale hydrogen production. However, the promising design of mixed matrix membranes (MMMs) that aims to integrate the molecular‐sieving properties of nanoporous architectures with industrial processable polymers still faces performance and fabrication issues due to the formation of segregated nanofiller domains in their polymer matrices. Here, an unconventional nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. 27,28 The cucurbit[n]uril (CB[n]) family of molecular containers 29−31 displays powerful host−guest binding abilities toward hydrophobic cations in water, 32−36 which isolates the guests from the external environment. 37,38 Viologens and their derivatives are popular components of CB[n] (n = 7, 8)based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. 27,28 The cucurbit[n]uril (CB[n]) family of molecular containers 29−31 displays powerful host−guest binding abilities toward hydrophobic cations in water, 32−36 which isolates the guests from the external environment. 37,38 Viologens and their derivatives are popular components of CB[n] (n = 7, 8)based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Supramolecular compounds are considered to be advanced and efficient separation membrane building blocks due to the presence of intrinsic pores in their molecular structure. , The cucurbit­[ n ]­uril (CB­[ n ]) family of molecular containers displays powerful host–guest binding abilities toward hydrophobic cations in water, which isolates the guests from the external environment. , Viologens and their derivatives are popular components of CB­[ n ] ( n = 7, 8)-based complex functional systems like molecular machines, supramolecular polymers, and drug delivery systems. Accordingly, we envisioned that formation of the CB[7]-BABD rotaxane complex would suppress dimerization of BABD cation radicals and improve the performance of the resultant NF membranes incorporating CBs. , Previously, we have presented the first examples of IP processes featuring CB­[ n ] rotaxanes as monomers. We found that the water permeability was enhanced threefold by reconfiguring the reconstructing membrane surface. , The design of voltage-gated membranes incorporating CB­[ n ] rotaxane monomers and investigations of their stimuli–response behavior remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, porous SPNs were also synthesized using PBI and organic macrocyclic cavitands (OMCs) with cavity sizes of 3.4−9.6 Å to simultaneously enhance H 2 permeability and H 2 /CO 2 selectivity. 31,32 Nevertheless, the dispersion of the OMCs in industrial asymmetric membranes is yet to be demonstrated. SPNs of ion-coordinated PBI have demonstrated superior self-healing and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge in fabricating highperformance PBI-based MMMs is how to uniformly disperse nanoparticles in the polymer matrix via adjusting the size and surface chemistry of nanoparticles and optimizing fabrication protocols. [160][161][162][163][164] PBI/carbon nanotubes, PBI/graphene, and PBI/ graphene oxide, PBI/ZIF nanocomposites have motivated extensive research in the elds of supercapacitors, gas separation, strengthened materials, and fuel cells. 12 Since zeolitic imidazolate frameworks (ZIFs), a subfamily of metal-organic frameworks (MOFs), have characteristics of tailorable cavity sizes, high porosity and good affinity with polymers, exceptional thermal stability and outstanding chemical resistance, 161,165 high-performance PBI/ZIF MMMs have been molecularly designed to improve the H 2 separation performance at high temperatures.…”
Section: Mixed Matrix Pbi Composite Hfmsmentioning
confidence: 99%
“…21, the performance of PBI hollow ber membranes for H 2 /CO 2 separation has gradually surpassed the upper bound of 2008 Robeson's curves. 65,238 Other efforts have been made to (1) blend PBI with thermosets in order to improve the thermal stability, 239 (2) embed soluble organic macrocyclic cavitands (sulfocalixarenes, SCA) to form homogeneous PBI nanocomposite membranes with distinctly molecular-sieving nanocavities, 164,240 (3) grow a selective MOF layer on the PBI HFM surface, 241 (4) dope PBI membranes with a polyprotic acid to improve H 2 /CO 2 diffusivity selectivity, 40 (5) apply Pd alloy (PdAg and PdNi) nanowires in PBI mixed matrix membranes to increase hydrogen diffusivity and reduce Pd embrittlement and susceptibility to poisoning, 242 (6) control the degree of N-quaternization on PBI based polymeric ionic liquids (PILs) to improve CO 2 sorption and gas permeation, 243 and ( 7) carbonize PBI as a carbon molecular sieve (CMS) with greatly enhanced H 2 /CO 2 , O 2 /N 2 size-sieving ability. 244,245 These schemes may potentially enhance the separation performance of PBI-based HFMs if one can successfully and economically convert them from at-sheet congurations to hollow bers.…”
Section: Gas Separation For H 2 /Co 2 Separation At Elevated Temperat...mentioning
confidence: 99%